Surf features extraction in a computer vision system - Puyda, Volodymyr (Lviv Politechnic Publishing House, 2017)
We consider a microcontroller implementation of an algorithm for extracting SURF features of an object in a video stream to be used in a specialized computer vision system.
Keywords: computer vision; video stream; SURF features; image identification